Does inter-municipal cooperation help improve local economic performance? – Evidence from Poland - Monika Banaszewska; Ivo Bischoff; Aneta Kaczynska; Eva Wolfschütz (Philipps-University Marburg, School of Business and Economics, 2020)
This paper aims at testing whether inter-municipal cooperation (IMC) in policies to promote local business development has a positive impact on local economic performance. We apply two-way fixed effects as well as marginal structural models to a panel data set covering 1,849 Polish municipalities between 2007 and 2014. We use the unemployment rate and the rate of population growth as a proxy for local economic performance. Our results show a systematic effect of IMC on local economic performance. However, the results are contradictory. While IMC causes higher rates of population growth, they also cause higher rates of unemployment.
Keywords: D72; H77; H80; O10; 330; Inter-municipal cooperation; local business development; population decline; marginal structural models; Poland